ARTIFICIAL GROUND FREEZING METHODFOR SHAFT CONSTRUCTIONIN MADDHAPARA HARDROCK MINE, BANGLADESH: MINIMIZATIONOFITS COST - Jahan, Chowdhury S; Quamruzzaman, Chowdhury; Mazumder, Quamrul H; Haque, Talukder AHFMA (Biological Sciences - PJSIR, 2004)
The Korea South-South Cooperation Corporation (NAMNAM) used Artificial Ground Freezing (AGF) during 160 m depth shafts (cage and skip) construction in the Maddhapara Hardrock Mining Project (MHMP). The freezing design calculation for AGF operation showed that freezing wall thickness was satisfactory for both kaolin and sand layer at existing vertical ground pressure. But after AGF operation freezing status revealed that the ice wall thickness in skip shaft attained as per design, but in cage shaft the achieved thickness was more than the expected due to deviation from original design for freezing hole by NAMNAM i.e., drilling of 31 freezing holes instead of 32 for cage shaft. The ice-wall bonding had affected the whole rock mass of the inner diameter of cage shaft that became hard like rock, but this effect was not so intensive for the skip shaft towards the inner portion and did not create any severe problem. As a result the cage shaft was excavated with explosive (drilling blasting) involving additional time (3 months) and cost (US1,51,866), which NAMNAM could avoid by sinking an additional 160 m deep freezing hole during cage shaft construction with a cost of US18,045 and thus saving a total of US1,33,820 for the whole operation in MHMP.